(untitled) (Estudios de Historia de España, 2016)
The battle of La Higueruela (1431) was the most important military success in the Grenade frontier during the reing of John II of Castile. This military fact was a chance to celebrate several royal ceremonies. The study of these ceremonies reflects the political relations in the castilian court.